2016
DOI: 10.5935/0004-2749.20160061
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes in optic disc morphology, choroidal thickness, anterior chamber parameters, and intraocular pressure during Valsalva maneuver

Abstract: VM may cause transient changes in IOP, optic disc morphology, and anterior chamber parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Mete et al showed that VM decreases the central corneal thickness and anterior chamber depth while increasing IOP, pupil diameter, and lens thickness. Both Falcão et al and Mete et al found that VM does not change the subfoveal choroidal thickness. Khan et al showed that VM does not significantly change the pulsatile ocular blood flow in primary open angle and normal tension glaucoma .…”
Section: Discussionmentioning
confidence: 91%
“…Mete et al showed that VM decreases the central corneal thickness and anterior chamber depth while increasing IOP, pupil diameter, and lens thickness. Both Falcão et al and Mete et al found that VM does not change the subfoveal choroidal thickness. Khan et al showed that VM does not significantly change the pulsatile ocular blood flow in primary open angle and normal tension glaucoma .…”
Section: Discussionmentioning
confidence: 91%
“…Other investigations noted changes in the anterior segment, such as anterior chamber narrowing. 20,28,29 However, the choroidal thickness in the macular area did not change, and the anterior choroidal changes might have caused the increase in IOP during VM. 20,28,29 Contrary to these studies, others concluded that the VM causes an increase in choroidal thickness.…”
Section: Discussionmentioning
confidence: 92%
“…Physiological conditions may change the ACD measurement. Mete et al found that the valsalva maneuvers reduce it by anterior displacement of iridolenticular diaphragm during this exercise [17]. Pregnancy was found to vary ACD in the third trimester versus postpartum period; these changes were not statistically significant, but the changes were attributed to CT change as a response to stromal water retention by hormonal effect [18].…”
mentioning
confidence: 87%